The Relationship between Humanness and Knowledge Sharing in Malaysia Empirical Evidence from Malaysian Managers - Boom, Ilona H.; Pennink, Bartjan W. (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2012)
This paper explores whether there is a relationship between humanness and the willingness to share knowledge in Malaysia. Furthermore, the differences between the Malay, Chinese and Indian ethnicities are researched for the presence of humanness and the willingness to share knowledge. Two hundred and fourteen respondents from privately owned companies participated in this research showing that there is a strong relationship between humanness and knowledge sharing. However, the differences between the three ethnicities are small, which is a surprising finding. It can be concluded that people-oriented managers (one of the ways to express humanness) are more willing to share knowledge, and differences between ethnicities have no influence in this matter. From these results, it can be recommended to managers and organizations in Malaysia that they pay more attention and be aware of their management style.Stressing the humanness aspects more as they are described could improve the knowledge transfer within companies.